High initial FSH dosage reduces the number of available cleavage-stage embryos in a GnRH-antagonist protocol: Real-world data of 8,772 IVF cycles from China - Luo, Xiu; Pei, Li; He, Yao; Li, Fujie; Han, Wei; Xiong, Shun; Han, Shubiao; Li, Jingyu; Zhang, Xiaodong; Huang, Guoning; Ye, Hong (Frontiers in Endocrinology, 2022)
To evaluate the relationship between the initial follicle stimulating hormone (FSH) dose and the number of available cleavage-stage embryos in in vitro fertilization (IVF) cycles. We included 8772 fresh IVF cycles using a GnRH antagonist protocol at the Genetic and Reproductive Institution of Chongqing, P. R. China, from January 2016 to June 2021. Univariate linear regression was used to evaluate the associations between the initial FSH dosage ( 150, 187.5–200, 225, 250, or 300 IU) with the number of available cleavage-stage embryos on day 3. A two-factor linear regression model was applied to calculate the threshold effect of the initial FSH dosage on the number of available cleavage-stage embryos based on a smoothing plot. The initial FSH dose was negatively correlated with the number of available cleavage-stage embryos, independent of female age, body mass index, infertility factors, duration of infertility, anti-Müllerian hormone and basal FSH levels, antral follicle count and the proportions of patients with poor ovarian response or polycystic ovarian syndrome. Using a two-factor linear regression model, we calculated the inflection point to be 200 IU of FSH. The relationship between the initial FSH dose and the number of available cleavage-stage embryos was nonlinear. The initial FSH dose was negatively associated with the number of available cleavage-stage embryos when the initial FSH dose was > 200 IU. Therefore, clinicians should try to avoid unnecessarily increasing the initial FSH dose.